Protocol for a Systematic Review of Rationing of Nursing Care - Mandal, Lata; Seethalakshmi, A.; Babu, Anitha Rajendra (Journal of Health and Allied Sciences NU, 2018)
Purpose: To identify and synthesize the findings of studies related to “rationing of nursing care”.Methods: Preferred Reporting Items for Systematic Reviews and Meta analysis (PRISMA) guidelines will be followed in this review and literature searches will be conducted in MEDLINE, CINAHL, Psyc Info, Web of Science and EMBASE databases. Only quantitative studies meeting the predetermined inclusion criteria, quality standards and credibility will be synthesised using narrative synthesis.Results: A descriptive synthesis of the findings of the selected studies will be carried out which will be presented in narrative summary with statistical findings incorporated.Conclusion: This review will provide a synthesis of up to date evidence regarding the rationing of care by nurses. It will also support the hypothesis that rationing of care has effects on patients and nurses and explore relationship of rationing of care with patients and nursing outcome.
Keywords: Rationing; nursing care; missed care; unmet care; patient outcomes